The patriot [videorecording] - Rodat, Robert; Emmerich, Roland ([S.l] : Global Entertainment Productions, 2000)
In the emotionally-charged adventure THE PATRIOT Academy Award winner Mel Gibson (Best Director, Best Picture BRAVEHEART 1995) stars as Benjamin Martin, a reluctant hero is swept into the American Revolution when the war reaches his home and threatens his family. A hero of the fierce French and Indian conflict, Martin had renounced fighting forever to raise his family in peace. But when the British arrive at his South Carolina home and endanger what he holds most dear, Martin takes up arms alongside his idealistic patriot son, Gabriel (Heath Ledger of 10 Things I Hate About You), and leads a brave rebel Militia into battle against a relentless and overwhelming English army. In the process, he discovers the only way to protect his family is to fight for a young nation's freedom.